RELATIONSHIP BETWEEN ENVIRONMENTAL STRESS FACTORS AND WORKER PERFORMANCE UNDER WELDING JOB ACTIVITY - M.A., M. Said; S.Z., You; N.K, Khamis; M.A.M., Sabri; A.R., Ismail; A., Ardiyanto (2023)
Environmental stressors in the welding industry are a significant concern for worker safety and health. To enhance worker performance, it is crucial to create a better workplace environment that ensures safety and health standards are met. To address these issues, this study aims to identify the correlation between these stress factors and worker performance, subsequently formulating a model equation to represent this relationship. Two primary methods were employed: subjective assessment and physical assessment. For physical assessment, data related to heat stress, relative humidity stress, and lighting stress were collected. Concurrently, a questionnaire containing 56 questions was developed and distributed for subjective assessment. A total of six welding industries participated, involving 15 respondents. All collected data were then analyzed using Pearson correlation and multivariate regression analysis to determine the study's relationship. The results of the multivariate regression analysis revealed a robust correlation value (R = 0.903) and a regression value (R square = 0.816). This variable provides a model that can be utilized to predict a worker's performance level and assess optimal job performance. In conclusion, this study can be valuable for relevant parties seeking to mitigate risks to worker safety in the workplace.